1995
DOI: 10.1091/mbc.6.2.185
|View full text |Cite
|
Sign up to set email alerts
|

The cyclosome, a large complex containing cyclin-selective ubiquitin ligase activity, targets cyclins for destruction at the end of mitosis.

Abstract: The ubiquitin-mediated degradation of mitotic cyclins is required for cells to exit from mitosis. Previous work with cell-free systems has revealed four components required for cyclin-ubiquitin ligation and proteolysis: a nonspecific ubiquitin-activating enzyme E1, a soluble fraction containing a ubiquitin carrier protein activity called E2-C, a crude particulate fraction containing a ubiquitin ligase (E3) activity that is activated during M-phase, and a constitutively active 26S proteasome that degrades ubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
591
2
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 710 publications
(613 citation statements)
references
References 43 publications
(55 reference statements)
9
591
2
7
Order By: Relevance
“…Plk1 is also thought to play a role in priming sister chromatids for separase cleavage by phosphorylating the SCC1 cohensin subunit after spindle assembly checkpoint inactivation (van Gugt and Medema, 2005). During metaphase APC/Cdc20 also ubiquitylates Cyclin B, the following destruction of Cyclin B inactivates Cdk1 (Glotzer et al, 1991;Sudakin et al, 1995;Peters, 2006).…”
Section: Figure 13 Cdk1 Activation Pathwaymentioning
confidence: 99%
“…Plk1 is also thought to play a role in priming sister chromatids for separase cleavage by phosphorylating the SCC1 cohensin subunit after spindle assembly checkpoint inactivation (van Gugt and Medema, 2005). During metaphase APC/Cdc20 also ubiquitylates Cyclin B, the following destruction of Cyclin B inactivates Cdk1 (Glotzer et al, 1991;Sudakin et al, 1995;Peters, 2006).…”
Section: Figure 13 Cdk1 Activation Pathwaymentioning
confidence: 99%
“…In addition to a classical E3 such as Ubr1, and the HECT domaincontaining proteins (Huibregtse et al 1995;Varshavsky 1996), novel E3s have been identified as crucial regulatory factors for cell cycle progression. These include the APC/cyclosome (the Anaphase Promoting Complex, Hershko et al 1994;Irniger et al 1995;King et al 1995;Sudakin et al 1995) and the SCF complex (Skp1-Cullin-1/Cdc53-F-box, Feldman et al 1997;Skowyra et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A condensed list of these moderators includes various cyclins (Sudakin et al, 1995), the tumor suppressor protein p53 , cdc25 (Nefski and Beach, 1996), c-mos (Ishida et al, 1993) and the cyclin-dependent kinase inhibitor p27 Kip1 (Pagano et al, 1995). The proteasome also regulates the timed degradation of important transcription factors including c-jun (Trier et al, 1994), c-myc (Ciechanover et al, 1991) and STAT1 (Kim and Maniatis, 1996).…”
Section: Introductionmentioning
confidence: 99%